Think Talk Write Model Improves Student Learning Outcomes in Islamic Education - Nurfuad, Muhamad; Bahri, Saiful; Azizah, Nurul; Rahmatika, Zahra; Susilawati, Beti (Indonesian Journal of Innovation Studies, 2025)
General Background: Effective learning strategies are critical in enhancing student engagement and academic outcomes, particularly in Islamic Religious Education (PAI), which requires both cognitive and affective comprehension. Specific Background: The Think, Talk, Write (TTW) model fosters active learning through sequential stages—critical reflection, collaborative discussion, and synthesis in writing. Knowledge Gap: Despite its theoretical potential, empirical studies evaluating the TTW model's effectiveness in the context of Islamic education, especially at the junior high school level, remain scarce. Aim: This study investigates the impact of the TTW model on students' learning outcomes in PAI at SMP Negeri 16 Bandar Lampung. Results: Using a quasi-experimental design with simple random sampling, students in the experimental group (Class A) showed significantly higher achievement compared to the control group (Class C), with an independent t-test significance of 0.006 (<0.05). Novelty: This study contributes novel insights by applying the TTW model to Islamic education and assessing its cognitive impact based on Bloom’s taxonomy. Implications: The findings suggest that TTW enhances critical thinking, communication, and comprehension in PAI, supporting its adoption as an effective pedagogical strategy in similar educational contexts. Highlights: Enhances students' critical thinking and engagement. TTW outperforms conventional teaching methods. Fills research gap in Islamic Education strategies. Keywords: Think Talk Write, Learning Outcomes, Islamic Education, Critical Thinking, Junior High School